P667 Standard vs. intensified infliximab rescue therapy for hospitalised paediatric patients with acute severe exacerbations of colitis-predominant inflammatory bowel disease. (16th January 2018) - Singh, K S; Hart, L; Al Khoury, A; Chao, C -Y; Afif, W; Lakatos, P L; Ahmed, N; Bessissow, T
Abstract: Background: The use of infliximab (IFX) rescue therapy for hospitalised patients with acute severe colitis is increasingly employed for steroid-refractory disease. Practice guidelines exist for acute severe ulcerative colitis (UC); however, there are no equivalent guidelines for Crohn's disease (CD). The aim of the study was to determine the efficacy of IFX induction regimens as rescue therapy for acute severe colitis-predominant CD, UC, and indeterminate colitis (IC) in a paediatric cohort, by assessing clinical and biochemical markers; and to identify predictors of favourable outcomes. Methods: We performed a retrospective review from January 2010 to December 2015 at the Montreal Children's Hospital. Hospitalised patients who received IFX rescue therapy for acute severe colitis were identified through in-patient pharmacy records. We compared standard induction of 5 mg/kg at 0, 2, and 6 weeks with intensified induction of 10 mg/kg and/or a short induction at 0.1 and 4 weeks. The primary outcome was clinical remission at 3 and 12 months, defined as an abbreviated paediatric CD activity index of <10 or a paediatric UC activity index <10. Secondary outcomes were colectomy-free remission at 3 and 24 months, and rate of Clostridium difficile infection at 12 and 24 months post-induction. Baseline parameters and dosing regimens were examined with regression analysis. Results: We identified 30 patients who met inclusion criteria; 21 CD, 2 UC, and 7 IC, mean (SD) age 14.8 (1.9) years. Nineteen (63.3%) received standard induction and 11 (36.7%) received intensified induction. Baseline mean (SD) C-reactive protein was 46.3 (35) mg/l, haemoglobin was 87.3 (22) g/l, and albumin was 24.4 (7.3) g/l. Time to normalisation was a mean (SD) of 4.8 (9.8), 23.4 (36.2), and 14.4 (26.4) weeks, respectively. The mean (SD) intravenous corticosteroid duration was 8.9 (8.8) days. There was no significant difference in these parameters between groups. Comparing the standard and intensified groups, there was no significant difference in clinical remission rates at 3 and 12 months (42.1% vs. 60%, p = 0.45 at 3 months and 15.8% vs. 33.3%, p = 0.63 at 12 months). There was no significant difference in colectomy rates at 3 months (21.1% vs. 18.2%, p = 1) and 24 months (21.1% vs. 27.3%, p = 1). There was a significantly higher rate of C. difficile infections in the intensified IFX group (45.5% vs. 5.3%, p = 0.01). Conclusions: In hospitalised paediatric patients with acute severe colitis, an intensified IFX regimen does not lead to improved short- or medium-term clinical or biochemical outcomes, but leads to higher rates of C. difficile infection. Further prospective studies assessing predictors of poor outcomes and a selective approach to intensified IFX therapy is warranted.